Characterising radio telescope software with the Workload Characterisation Framework - Grange, Y; Lakhoo, R; Petschow, M; Wu, C; Veenboer, B; Emsley, I; Dijkema, T; Mechev, A; Mariani, G (Astronomical Society of the Pacific, 2019)
We present a modular framework, the Workload Characterisation Framework (WCF), that is developed to obtain, store and compare key characteristics of radio astronomy processing software in a reproducible way. As a demonstration, we discuss the experiences using the framework to characterise a LOFAR calibration and imaging pipeline.